The wheels on the bus - Ziefert, Harriet; Baruffi, Andrea (New York : Random House, 1990)
The wheels on the bus go round, the wipers go swish, the doors open and close, and the people go in and out in this rollicking version of the classic song.
Keywords: Children's songs -- Texts; Buses -- Songs and music; Songs